PERFORMANCE AND PHYSIOLOGICAL RESPONSES OF BROILER CHICKENS TO DIETARY COMBINATION OF YEAST AND MEDICAL PLANTS. - Beski, S. S. M.; M’Sadeq, S. A.; Hussein, S. M.; Mahmod, A. L. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This feeding trial was conducted to investigate the effect of medical plants and yeast cell wall on the performance and subsequent physiology of broiler chickens. A total of 200 d-old Ross 308 broiler chicks were randomly allocated to 5 treatments that were replicated 4 times of 10 birds. The first treatment was the control while the remaining four treatments were supplemented with one of these mixtures (peppermint and Chamomile; peppermint powder and yeast cell wall; chamomile powder and yeast cell wall; peppermint, yeast cell wall and chamomile powder). Throughout the experimental period, feed intake was almost not affected by dietary treatments. At days 24 and 35 of age, birds on diets containing mixtures of herbal plants or herbal plants with yeast gained more weight than the control group. Feed conversion ratio of the 24 d-old broilers was significantly improved by the combination of herbal plants and its combination with yeast. However, when assessed over the 35 d experimental period, it was almost same among all experimental units. The relative weight of visceral organs and bursal morphology were not affected by dietary treatments. Significantly lower serum cholesterol and longer jejunum villi were detected in birds that were offered diets supplemented with mixture of herbal plants alone or its combination with yeast.